Software Solutions for the Analysis of the Innovation Capability of the Company. (2015) - Alexe, Cătălin-George; Alexe, Cătălina-Monica
Abstract: This paper aims to develop a brief overview of IT solutions to support the analysis of the innovation capability of a firm, which at first sight are not so many and are generally grouped in the German-speaking area, where there are serious and visible concerns in this direction. In this regard, there are mentioned the solutions offered by IMP 3 rove, InnoScore, TCW Innovationsaudit. Software solutions dedicated to the analysis of the innovation capabilities that have occurred in recent years in the world, come to eliminate these shortcomings by providing the possibility of obtaining various management reports particularly useful in managing innovation in a company. Thus, it can perform internal and external benchmarking and, not at least, safety data is made easier. Many IT solutions are solutions identified online free that can be useful for entrepreneurs and managers, with the possibility of comparing results of the analyzed company to other companies' performances in the European space.